SUSTAINABILITY BLUE DISCLOSURES: INDEX DEVELOPMENT AND PRELIMINARY IMPLEMENTATION - Derry Wanta; Juniati Gunawan (JRAK, 2021)
The aim of this paper is to develop a sustainability blue disclosure index and evaluating the implementation to provide preliminary findings through the information disclosed in annual reports. This disclosure considers blue economy activities namely Sustainability Blue Disclosures (SBD). A qualitative approach was applied in this study by the content analysis method. This research uses saturated sampling, taken all available annual reports from the listed fisheries and marine companies from 2015 to 2019 at the Indonesia Stock Exchange. These results may indicate that the companies are in the early stage to understand sustainability issues, including the availability and quality of raw materials, changing of environmental quality, working capital performance, fluctuation of the foreign exchange rate, and demand from the global markets.